Analysis of Environmental Health Quality Supervision Training forEnvironmental Sanitation Officers at Public Health Centers and theSamarinda City Health Office - Rima Andriani (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Law No. 17 of 2023 concerning Health states that to achieve the highest attainable standard of public health, health efforts must be carried out in an integrated and comprehensive manner through individual and community health services. Environmental health is an effort to prevent diseases or health disorders caused by environmental risk factors (physical, chemical, biological, and social). Therefore, it is necessary to conduct training on environmental health quality supervision for Environmental Sanitation Officers at Public Health Centers (PHC). These officers are health human resources who specifically perform environmental sanitation tasks. Consequently, capacity building for Environmental Sanitation Officers is essential to ensure their professionalism and to support the effective implementation of environmental health programs at PHC in accordance with national performance indicators. Objective : To assess the difference in sanitation knowledge scores before and after the environmental health quality supervision training among Environmental Sanitation Officers at PHC and the Samarinda City Health Department. Research Methods/ Implementation Methods : This study employed a pre-experimental design using a one-group pretest–posttest approach. The statistical analysis was conducted using the Wilcoxon signed-rank test. Results : Among the 30 respondents, 7 were male and 23 were female. The results indicated an increase in knowledge scores after the training compared to before. The Wilcoxon signed-rank test showed a significant effect of the training on the sanitation officers’ knowledge, with a p-value of 0.001 (< 0.05). Conclusion/Lesson Learned : There was a significant difference in sanitation officers’ knowledge before and after the environmental health supervision training at PHC and the Samarinda City Health Department, indicating that the training had a positive impact.